High prevalence of HIV-1 transmitted drug resistance and factors associated with time to virological failure and viral suppression in Taiwan. (14th October 2021) - Huang, Szu-Wei; Shen, Mei-Chen; Wang, Wen-Hung; Li, Wei-You; Wang, Jen-Hsien; Tseng, Cheng-Yin; Liu, Po-Yu; Wang, Lih-Shinn; Lee, Yu-Lin; Chen, Yi-Ming Arthur; Lee, Chun-Yuan; Lu, Po-Liang; et al.
Abstract: Background: Integrase strand transfer inhibitor (InSTI)-based regimens have become the major first-line treatment for HIV-1-infected patients in Taiwan. Transmitted drug resistance (TDR) and several clinical characteristics are associated with time to virological failure or viral suppression; however, these have not been investigated in Taiwan. Objectives: To determine the impact of several factors on treatment outcomes in HIV-1-infected patients in Taiwan. Methods: The cohort included 164 HIV-1 treatment-naive patients in Taiwan from 2018 to 2020. Blood specimens were collected to determine the genotypic drug resistance using the Stanford University HIV drug resistance database. Cox proportional hazards models were used to identify factors associated with time to virological failure or viral suppression. Results: The prevalence of TDR in Taiwan was 27.4% and an increasing trend was seen from 2018 to 2020. TDR mutations related to NNRTIs were the most prevalent (21%) while TDR to InSTIs remained at a relatively low level (1.3%). A baseline HIV-1 viral load of ≥100 000 copies/mL was associated with a shorter time to virological failure [multivariate hazard ratio (mHR) 7.84; P   =  0.018] and longer time to viral suppression (mHR 0.46; P   <  0.001). Time to viral suppression was shorter in patients receiving InSTI-based regimens (mHR 2.18; P   =  0.006). Different InSTI-based regimens as initial treatment did not affect the treatment outcomes. Conclusions: This study found an increasing trend of HIV-1 TDR prevalence from 2018 to 2020 in Taiwan. Baseline HIV-1 viral load and receiving InSTI-based regimens are important factors associated with time to virological failure or viral suppression.